citizens versus the new public manager: the problem of mutual empowerment - Peters, B. Guy; Pierre, Jon (2000)
Many contemporary reforms of the public sector advocate empowerment as a solution for many of the problems of governing. The difficulty arises when different groups - clients, lower-level officials, senior officials, and local communities - are all the subject of empowerment. Attempts to enhance the power of all these players in the policy process is argued to create the probability of political conflict, and this is demonstrated with a set of examples. Efforts at empowerment further may be the sources of substantial disillusionment and possible alienation when it becomes apparent that all groups cannot be empowered at once. - Reproduced
Keywords: Public administration